Evidence-based prescription for cyclo-oxygenase-2 inhibitors in sports injuries - D.C. Janse van Rensburg; A. Jansen van Rensburg; C.C. Grant; P. Zondi (South African Family Practice, 2015)
Healthcare professionals are increasingly under pressure to return athletes to play in the shortest possible time. There is limited choice in providing treatment that speeds up tissue repair, while simultaneously maintaining good quality of healing. Inflammation forms a fundamental part in the process of tissue repair. However, excessive inflammation may cause more pain, and limit functional restoration. Although the use of anti-inflammatory treatment in the form of a cyclo-oxygenase-2 inhibitor (coxibs) has been widely recognised as being effective, the potential detrimental effect on tissue repair, as described mainly in animal model studies, needs to be taken into account. The side effects profile on the gastrointestinal tract favour coxibs over non-traditional NSAIDs. The possible effects on the renal and cardiovascular systems also need to be considered. The prescription of coxibs should be pathology and situation specific. There are no clear guidelines on the correct time of administration and the duration of the course, but it seems that the literature is in agreement that they should be administered for a limited time at the lowest effective dose possible.